Blood conservation strategies and the management of perioperative anaemia. Issue 3 (June 2015) - Shander, Aryeh; Javidroozi, Mazyar
<x xml:space="preserve">Abstract</x> Purpose of review Anaemia is a global health problem with particularly high prevalence in the perioperative setting and it can significantly affect the patient outcomes. This review addresses new findings on the significance of anaemia and patient blood management (PBM) strategies to prevent and manage anaemia. Recent findings Studies support the independent deleterious effects of anaemia on mortality, morbidity and quality of life as well as its role as a risk factor for transfusion. Although improved understanding of iron regulators such as hepcidin is expected to revolutionize the field, simple algorithms are useful tools for more effective management of anaemia relying on currently available therapies (such as intravenous iron and erythropoiesis-stimulating agents). Other PBM strategies such as optimization of haemostasis and avoidance of blood loss are effective in preventing anaemia or its exacerbation and improving the outcomes of patients. In addition, more attention should be given to hospital-acquired anaemia (HAA) and its avoidable causes, such as unnecessary diagnostic phlebotomies. Summary Despite the high prevalence of anaemia and the significant toll it takes on patients, simple and effective strategies are available to detect, diagnose and treat it.